A New Microfluidic Chip‐Based Online Electrochemical Platform for Extracellular Neurochemicals Monitoring in Rat Brain. Issue 4 (11th March 2013) - Lin, Yuqing; Lu, Xulin; Gao, Xia; Cheng, Hanjun; Ohsaka, Takeo; Mao, Lanqun
Abstract In this study, we report a simple microfluidic chip‐based technique as an effective online electrochemical platform for continuous monitoring of neurochemicals in rat brain by using ascorbate as an example. To establish the platform for neurochemical monitoring, a single‐channel microfluidic chip is developed into an electrochemical cell by incorporating an indium‐tin oxide (ITO) electrode as working electrode, an Ag/AgCl wire as reference electrode, and a Pt tube as counter electrode. The selective detection of ascorbate is accomplished by dip‐coating single‐walled carbon nanotubes (SWNTs) onto the ITO electrode. As reported in our early studies, the use of SWNTs largely facilitates the electron transfer of ascorbate, well differentiating the potential for the ascorbate oxidation from those for other kinds of electrochemically active neurochemicals existing in the cerebral systems. With the microfluidic chip‐based electrochemical cell as selective detector, an online electrochemical detecting system is established by directly integrating the microfluidic chip‐based electrochemical detector with in vivo microdialysis. The system is demonstrated to have a good linear response toward ascorbate, high stability, and good in vivo reproducibility and stability. These excellent properties substantially enable this system to be particularly useful for continuous monitoring of ascorbate in rat brain.